2020
DOI: 10.1111/dth.13834
|View full text |Cite
|
Sign up to set email alerts
|

Acute generalized exanthematous pustulosis induced by empiric hydroxychloroquine for presumed COVID ‐19

Abstract: stable. She was transitioned to an oral prednisone taper to further treat her active but improving rash. A skin biopsy, collected prior to treatment, showed a subcorneal pustule with neutrophils and eosinophils consistent with a diagnosis of acute generalized exanthematous pustulosis (Figure 2). The rash resolved with the prednisone taper after 38 days. The rapid spread of COVID-19 has left health care providers across the world in search of treatment options to combat the virus. This case highlights a severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 8 publications
0
9
0
3
Order By: Relevance
“…We have evaluated 20 case reports including 25 cases of COVID‐19 who were treated with multiple drugs in Table 1 4‐23 . In Tables 2, 4 cohort studies are shown.…”
Section: Resultsmentioning
confidence: 99%
“…We have evaluated 20 case reports including 25 cases of COVID‐19 who were treated with multiple drugs in Table 1 4‐23 . In Tables 2, 4 cohort studies are shown.…”
Section: Resultsmentioning
confidence: 99%
“…In case of HCQ‐induced AGEP, the latency period appears to be longer (ranging from 4 to 30 days 6 ) than in antibiotics‐related cases, and the eruption tends to be more serious and resistant to treatments. 7 , 8 A differential diagnosis could have been HCQ‐induced generalized pustular figurate erythema (GPFE), which has been recently described in two patients with COVID‐19; 9 however, our patient was febrile and the cutaneous presentation was more consistent with AGEP than GPFE.…”
Section: Figurementioning
confidence: 99%
“…Además de la activación de estos virus, las repuestas inmunológicas antivirales y las respuestas inmunológicas contra los medicamentos pueden ser los mecanismos productores de las reacciones que estamos observando en los enfermos con COVID-19. 20,21 AGEP: PUSTULOSIS SUBCÓRNEA AGUDA EXANTEMÁTICA La pustulosis aguda subcórnea es una reacción medicamentosa que corresponde al grupo de las severas. Múltiples medicamentos han sido implicados en su génesis incluyendo los antipalúdicos de síntesis.…”
Section: Dress (Exantema Eosinofilia Y Síntomas Sistémicos Inducido Por Fármacos)unclassified
“…Múltiples medicamentos han sido implicados en su génesis incluyendo los antipalúdicos de síntesis. Enos T y colaboradores 21 describieron el caso de una mujer de 29 años de edad, con antecedente de deficiencia en la proteína S y un supuesto síndrome de Stevens-Johnson debido al cefaclor. Tuvo un contacto cercano con portador de SARS-CoV-2, se presentó refiriendo hipertermia, tos y dolor de garganta.…”
Section: Dress (Exantema Eosinofilia Y Síntomas Sistémicos Inducido Por Fármacos)unclassified
See 1 more Smart Citation